Standardization of in vitro pollination and fertilization technique for heliconia - Dhanya A (Department of Pomology and Floriculture, College of Agriculture, 2006)
Investigations on “Standardization of in vitro pollination and fertilization technique for heliconia” were carried out at the Department of Pomology and Floriculture utilizing the facilities available at plant tissue culture laboratory Department of Plant Biotechnology, College of Agriculture, Vellayani during 2005-2006 with the objective to standardize various steps of in vitro pollination technique in heliconia. Three cultivars of Heliconia psittacorum viz., Lady Di, Andromeda and Parakeet were selected for the study. The mean pollen fertility with acetocarmine stain in the selected cultivars was high ranged which from 83.61 to 93.04 per cent. Attempts to develop a medium which will support pollen germination and tube growth in heliconia resulted in the identification of ME3 medium with 12 per cent PEG. The pH reaction ranging from 4 to 8 did not influence the pollen germination. Pollen germination started within ½ h of incubation and continued upto 3 h. Regarding pollen germination, ME3 medium with 12 per cent PEG, cultivar Lady Di recorded highest germination per cent (62.08 %) followed by Andromeda (56.72 %) and Parakeet (54.37 %). Among the selected cultivars, there was no significant difference in morphological characters of gynoecium. Successful in vitro pollination was obtained when the flower buds were collected one day before anthesis and pollination done at the time of anthesis. The flower buds surface sterilized with 0.1 per cent mercuric chloride for three minutes, followed by inoculation in the medium containing 25 mg l-1 Copper Sulphate registered 100 per cent survival of the cultures. MS medium was superior to ½ MS, SH and Nitsch medium with respect to the ovule development when supplemented with growth regulators. Among the various methods of pollination, ovule development and seed set was observed in placental pollination, modified placental pollination and test-tube fertilization. In all these cases pollen grains along with pollen germination media were applied over the ovule. In the case of stigmatic pollination, stylar pollination, ovarian pollination and intra-ovarian pollination, there was ovary development, but none of them showed ovule development. Among the successful in vitro pollination techniques, modified placental pollination was found to be convenient and recorded maximum ovule development in heliconia. Studies of three different levels (3, 6 and 9 %) of sucrose showed that three per cent sucrose was superior for ovule development. Among the auxins, NAA was found to be superior to IAA. The combination treatments of auxin and cytokinin were found to be superior to their individual effect. Among these, combination of BA with NAA was seen to be better in promoting ovule development. The treatment BA 2.5 mg l-1 + NAA 2 mg l-1 was recorded highest ovule development in heliconia after in vitro pollination. Other supplements like CH (500 mg l-1) and YE (250 and 500 mg l-1) enhanced ovule development along with auxin and cytokinin. However in the present study, coconut water (5, 10, 15 and 20 % v/v) did not support the ovule development after in vitro pollination. Solid medium supported the ovule development after in vitro pollination than liquid medium. Cultures kept at 26  2C developed seeds under diffused light condition. In vitro formed seeds of heliconia were elongated oval shape. The colour of the seed was light brown in the initial 20 days, turned brown within 40-60 days and become completely black after 90 days. The seed measured 1800 m in length and 1575 m in breadth. The histological examination of ovules showed well developed endosperm and embryo. The embryo seated at chalazal end and three progressive stages of embryos were identified viz., globular, reniform and elongated shape. The embryos become dead 90 days after pollination when they were retained in the seeds. Hence attempts have been made to integrate in vitro pollination and fertilization and embryo rescue. When 40 days old embryos were cultured in MS medium with three per cent sucrose, germination indices were observed 60 days after embryo culture, kept at 26  2C in dark.